Choice of the Retention Method After an Orthodontic Treatment-Rewiev - Jelešković, Azra; Redzepagic-Vrazalica, Lejla; Dzemidzic, Vildana; Tiro, Alisa; Nakas, Enita (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2020)
Retention is a phase of orthodontic treatment devised to keep the teeth in a correct position once the orthodontic treatment has been completed. There are three main characteristics that each ideal retainer is required to have: to keep the teeth in the correct position after orthodontic therapy, to be long lasting and resistant to mechanical damage, and to have no adverse long-term effects on periodontal tissue. Through a computer-based browsing through a number of databases (such as, e.g. PubMed and Google Scholar) we have found and analysed various articles used in this research. The inclusion criteria to be met were: an overall availability of a research paper, the requirement that these research papers are published in English, that these research papers were published in the period 2007-2019, the requirement that the research papers should involve clinically randomized studies and that their titles contain one of the predefined keywords. The database browsing that is based on the said keywords and carried out within the above time frame has resulted in finding 165 relevant articles. A complete set of the inclusion criteria were met by 8 published research papers, but 7 articles were analysed in the end. The selected articles have compared different types of fixed and mobile retainers, different times of wearing the retainers, the impact that the retainers had on the periodontium, and the acceptability of different retention protocols for patients. The conclusion of this research paper is that bonded retainers prove to be most effective in stabilising the position of the incisors, particularly the lower ones, but that their disadvantages include the reopening of the extraction space and the retention of plaque due to difficulties in maintaining oral hygiene. Vacuum-formed retainers appear to be more effective than Hawley retainers in retaining the position of the incisors, and patients have indicated that they are more acceptable to wear. Hawley retainers prove to be most effective in preserving a closed extraction space, but they do now show solid results with regard to other segments. Changes in the overbite, overjet, arch length, and anterior and posterior widths did not show any significant statistical differences in the different types of retainers. Keywords: orthodontics, retention, stability, impact